VIRILISATION SECONDARY TO LEYDIG CELL OVARIAN TUMOR IN A POSTMENOPAUSAL WOMAN WITH PRIMARY HYPERPARATHYROIDISM - Sern, Gan Chin; Vergis, Melissa; Hsien, Chua Chia (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Ovarian sex cord-stromal tumors, which include steroid cell tumors, comprise 5–8% of all ovarian tumors. Less than half are androgen-secreting. Leydig cell tumors are a type of steroid cell tumor. They are usually androgen-secreting, unilateral, and can be either benign or malignant. We report a case diagnosed in a postmenopausal woman during follow-up for primary hyperparathyroidism. CASE A 66-year-old female was noted to have significant hirsutism during a follow-up consult for hyperthyroidism, which reportedly started in the past 5 years. She had primary hyperparathyroidism secondary to right inferior parathyroid adenoma for the last 10 years, not fulfilling criteria for surgery. Her other comorbidities were rheumatoid arthritis diagnosed at age 50; as well as diabetes mellitus, hypertension, dyslipidaemia and fatty liver disease, diagnosed between 54 to 62 years of age. She had 3 children and experienced early menopause at age 42. She had frontal balding and terminal hair growth on chest, back, abdomen, face and limbs. Systemic examination was unremarkable. Testosterone level was 14.8 nmol/L (normal range 0.24–1.70) while dehydroepiandrosterone sulfate (DHEAS) level was normal. CT imaging noted an enhancing focus in the left ovary (0.8 x 1.1 x 1.4 cm). She underwent exploratory abdominal hysterectomy with bilateral salpingo-oophorectomy, appendectomy and omental biopsy which revealed Leydig cell tumor of the left ovary, with intact capsule. Two months post-operatively, testosterone was undetectable (<0.087 nmol/L) and the patient reported reduced facial hair growth. CONCLUSION The development of true hirsutism, alopecia, and/or acne in postmenopausal women should not be disregarded, and assessment for causes of postmenopausal hyperandrogenism should be undertaken. This case illustrates a rare co-existence of an androgen-secreting ovarian tumour with concomitant long-standing primary hyperparathyroidism.